Changes Experienced by Low-Concentration Lipid Bicelles as a Function of Temperature - Alahmadi, Ibtihal (Langmuir : the ACS journal of surfaces and colloids, 2022)
Differential scanning calorimetry (DSC) of dipalmitoyl phosphatidylcholine (DPPC), dihexanoyl phosphatidylcholine, and dipalmitoyl phosphatidylglycerol bicelles reveals two endothermic peaks. Based on analysis of small angle neutron scattering and small angle X-ray scattering data, the two DSC peaks are associated with the melting of DPPC and a change in bicellar morphology─namely, either bicelle-to-spherical vesicle or oblate-to-spherical vesicle. The reversibility of the two structural transformations was examined by DSC and found to be consistent with the corresponding small angle scattering data. However, the peak that is not associated with the melting of DPPC does not correspond to any structural transformation for bicelles containing distearoyl phosphatidylethanolamine conjugated with polyethylene glycol. Based on complementary experimental data, we conclude that membrane flexibility, lipid miscibility, and differential solubility between the long- and short-chain lipids in water are important parameters controlling the reversibility of morphologies experienced by the bicelles